Risk Factors Associated with Postpartum Ovarian Vein Thrombosis - Salomon, Ophira; Apter, Sara; Shaham, Dorith; Hiller, Nurith; Bar-Ziv, Jacob; Itzchak, Yacov; Gitel, Sanford; Rosenberg, Nurit; Strauss, Simon; Kaufman, Nathan; Seligsohn, Uri (Thrombosis and Haemostasis, 1999)
Thrombosis of the ovarian vein is a remarkable process occuring within a few days of labor in 1:500-1:2000 women. Its presentation is characterized by fever, abdominal pain and occasionally by a palpable abdominal mass that in earlier years sometimes lead to explorative laparotomy. With the advent of modern imaging techniques the diagnosis can be made relatively easily. The pathogenesis has been attributed to an infectious process expanding from the uterus to the right ovarian vein and stasis. A predisposition towards thrombosis has not been so far explored. In this study we retrospectively analysed the clinical features, diagnosis and treatment of 22 patients with objective documentation of post partum ovarian vein thrombosis (POVT) and assessed potential risk factors. In 11 of the 22 patients (50%) inherited prothrombotic risk factors were detected as follows: 4 were heterozygous for factor V G1691 A, 2 had protein S deficiency, one had protein S deficiency and was heterozygous for factor V G1691A, and 4 were homozygous for MTHFR C677T. Eight of the 11 patients who bore a prothrombotic predisposition underwent cesarean section. Taken together, the data suggest that POVT may result from the combined effect of an infection, cesarean section and a prothrombotic tendency.